2015
DOI: 10.3762/bjnano.6.35
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle shapes by using Wulff constructions and first-principles calculations

Abstract: Summary Background: The majority of complex and advanced materials contain nanoparticles. The properties of these materials depend crucially on the size and shape of these nanoparticles. Wulff construction offers a simple method of predicting the equilibrium shape of nanoparticles given the surface energies of the material. Results: We review the mathematical formulation and the main applications of Wulff construction during the last two decades. We then focus to three recent extensions: active sites of metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(182 citation statements)
references
References 63 publications
(62 reference statements)
3
162
0
5
Order By: Relevance
“…Due to crystal symmetry, the SAG on the [ 112¯0 ] lateral direction, which consists of (0001), {112¯2}, and {112¯0} planes, can also be considered. Details of the equilibrium Wulff construction are explained elsewhere . Furthermore, it is well known that the MOVPE condition, such as growth temperature, partial pressure, and carrier gas, is crucial for the equilibrium crystal shape in GaN nanostructures.…”
Section: Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to crystal symmetry, the SAG on the [ 112¯0 ] lateral direction, which consists of (0001), {112¯2}, and {112¯0} planes, can also be considered. Details of the equilibrium Wulff construction are explained elsewhere . Furthermore, it is well known that the MOVPE condition, such as growth temperature, partial pressure, and carrier gas, is crucial for the equilibrium crystal shape in GaN nanostructures.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Details of the equilibrium Wulff construction are explained elsewhere. [20,24,25] Furthermore, it is well known that the MOVPE condition, such as growth temperature, partial pressure, and carrier gas, is crucial for the equilibrium crystal shape in GaN nanostructures. In this study, these parameters are taken into account by constructing surface phase diagrams among various orientations as functions of growth temperature and partial pressure.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Historically, in 1874, 38 Gibbs suggested that the shape of a crystal is dictated by the minimization of the total surface energy. Therefore, the shape of crystals (and nanocrystals, as it has been shown that the equilibrium shapes of the macroscopic crystals and nanocrystals are the same when they have the same chemical composition 39,40 ) is therefore not dictated by the minimum total surface (which is a sphere), but depends strongly on crystalline facets. The final equilibrium shape will be dominated by the facets with the lowest surface energies.…”
Section: Figure 1: Evolution Of the Gibbs Free Energy Of A Cluster Vementioning
confidence: 99%
“…First-principles investigations have been recognized as effective for studying the morphology and surface properties of a wide variety of crystals and NCs [52][53][54]. Our group has developed a working methodology, which has been applied to the study of different morphologies in different metal oxides such as SnO 2 [55][56][57], PbMoO 4 [58], and CaWO 4 [59].…”
Section: State-of-the-art Developmentsmentioning
confidence: 99%